Material and social footprint of rooftop photovoltaics in the city of Vitoria-Gasteiz - Alex Tro-Cabrera; Alex Tro-Cabrera; Rosa Lago-Aurrekoetxea; Rosa Lago-Aurrekoetxea; Estitxu Villamor; Estitxu Villamor; Leire Urkidi-Azkarraga; Leire Urkidi-Azkarraga; Gorka Bueno; Gorka Bueno; Emmanuel Aramendia (Frontiers in Sustainable Cities)
Cities are key players in the current energy and climate crisis. Not only do they account for two-thirds of global final energy consumption and produce 75% of total greenhouse gas emissions, but they also offer opportunities to respond to these challenges through local actions, such as the installation of rooftop photovoltaic (RPV) systems. However, caution is needed to minimize the socio-environmental impacts that renewable deployment causes as well. This study analyses the implications of RPV in terms of primary extraction material requirements and environmental and social impacts using the city of Vitoria-Gasteiz (Spain) as a case study. Both environmental and social life cycle assessments (LCA) were performed by modeling the potential annual photovoltaic electricity production of 473 GWh found for Vitoria-Gasteiz, and comparing it to the same amount of electricity produced by the conventional Spanish electricity mix. We employed the openLCA software, with the ecoinvent 3.10 database and the soca v3 add-on module. The inventory of ecoinvent for RPV electricity production was updated in order to reflect the per capita primary extraction material requirements and compare them to population weighted global material reserves, resources and in-use stocks. A literature review is included to illustrate the socio-environmental impacts of mining. Results show a very high ratio of primary extraction requirements to reserves for gold (28.5%), silver (29.4%), and tin (56.2%). In addition, the deployment of RPV would increase the in-use stocks of silver by 12%, and the aluminum and tin stocks by 9%. Regarding silicon, despite its reserves being abundant, global polysilicon production capacity should be at least tripled in a 25-year scenario. Hence, recycling activities should be more than doubled to avoid an increase in mining. Environmental-LCA shows a significant reduction for all analyzed impact categories, especially climate change (79%), acidification (71%), and land (70%), and water use (63%). In contrast, social-LCA shows no substantial changes in risk levels, as the economic activity in photovoltaic supply chains remains largely concentrated in developing countries, generating similar social impacts. By acknowledging the socio-environmental trade-offs of renewable energies, cities can foster a fair energy transition that is both materially grounded and ecologically aware.